Framing of the Covid-19 pandemic and its organizational predictors - Frida V. Rodelo (Cuadernos.info)
The way in which the news media frame information can influence perceptions of public affairs among audiences and, therefore, the development of debates on these matters. This effect can be magnified in the face of health crises such as pandemics because people increase their media consumption in the face of issues that are unknown, related to their safety, and where multiple perspectives coexist. The study accounts for the news frames in the media coverage of the Covid-19 pandemic during the stage of increasing community transmission. It is based on a content analysis of national reach printed newspapers and newscasts in Mexico. The results show that the attribution of responsibility, human interest, and political actions frames predominated in the flow of information about Covid-19, while the scientific information and self-efficacy frames were kept to a minimum. The analysis suggests that media sector and political orientation were decisive factors for the construction of the health crisis in the media, as well as elements linked to journalistic routines, such as reporter beats, and the actors featured in the stories.